Comparison of the diagnostic ability of blue laser imaging magnification versus pit pattern analysis for colorectal polyps - Nakano, Arihiro; Hirooka, Yoshiki; Yamamura, Takeshi; Watanabe, Osamu; Nakamura, Masanao; Funasaka, Kohei; Ohno, Eizaburo; Kawashima, Hiroki; Miyahara, Ryoji; Goto, Hidemi (Endoscopy International Open, 2017)
Background and study aims There have been few evaluations of the diagnostic ability of new narrow band light observation blue laser imaging (BLI). The present prospective study compared the diagnostic ability of BLI magnification and pit pattern analysis for colorectal polyps.Patients and methods We collected lesions prospectively, and the analysis of images was made by two endoscopists, retrospectively. A total of 799 colorectal polyps were examined by BLI magnification and pit pattern analysis at Nagoya University Hospital. The Hiroshima narrow-band imaging classification was used for BLI. Differentiation of neoplastic from non-neoplastic lesions and diagnosis of deeply invasive submucosal cancer (dSM) were compared between BLI magnification and pit pattern analysis. Type C2 in the Hiroshima classification was evaluated separately, because application of this category as an index of the depth of cancer invasion was considered difficult. Results We analyzed 748 colorectal polyps, excluding 51 polyps that were inflammatory polyps, sessile serrated adenoma/polyps, serrated adenomas, advanced colorectal cancers, or other lesions. The accuracy of differential diagnosis between neoplastic and non-neoplastic lesions was 98.4 % using BLI magnification and 98.7 % with pit pattern analysis. In addition, the diagnostic accuracy of BLI magnification and pit pattern analysis for dSM for cancer was 89.5 % and 92.1 %, respectively. When type C2 lesions were excluded, the diagnostic accuracy of BLI for dSM was 95.9 %. The 18 type C2 lesions comprised 1 adenoma, 9 intramucosal or slightly invasive submucosal cancers, and 8 dSM. Pit pattern analysis allowed accurate diagnosis of the depth of invasion in 13 lesions (72.2 %). Conclusions Most colorectal polyps could be diagnosed accurately by BLI magnification without pit pattern analysis, but we should add pit pattern analysis for type C2 lesions in the Hiroshima classification.